Briefing paper on Agenda 21 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The International Service for National Agricultural Research (ISNAR) has produced a briefing paper which outlines some of the implications of Agenda 21 for national agricultural research systems (NARS) in developing countries. Although the document...